Key Macroeconomic Variables and Stock Market Development in Nigeria: Evidence from Granger Causality Test - Yusuf, Aminu; Gwadabe, Mohammed; Yahaya Ukashatu, Ali (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
The study examined the key macroeconomic variables on stock market development in Nigeria using the Granger causality test from Nigeria from 1986 to 2019. The study relies heavily on secondary data (time series) sourced from the various institutions. Data on GDP, money supply (M2), interest rate, and exchange rate were sourced from the Central Bank of Nigeria (CBN). Data of all share indices was sourced from the Securities and Exchange Commission (SEC) and the Nigerian Stock Exchange (NSE). Data on inflation was sourced from the National Bureau of Statistics (NBS). The statistical properties of data were tested using the ADF and PP tests. The test indicated that interest rate and trade openness are stationary at level, while all share index, money supply, exchange rate, and inflation rate are stationary at first difference. The Granger causality test indicates that there is bi-directional causality among the variables except for the exchange rate. Based on these findings, the study recommends that the Central Bank of Nigeria should ensure stability in the exchange rate by promoting trade, tourism, and foreign investment, and it recommends that the Central Bank of Nigeria and fiscal authorities should embark on liberalization policies and ease all trade barriers to encourage trade amongst its trading partners.